The Role Of Aqidah In Building Muslim Character In The Digital Era: A Theological And Psychological Perspective - Alpan Noor Habib Rangkuti; Rony Aspani; Asep Sopian (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This article explores the role of aqidah in shaping Muslim character in the digital era through the perspectives of theology and psychology. The study is motivated by a moral crisis amidst rapid technological advancements. Through a literature-based approach, the study highlights aqidah as the foundation of Islamic beliefs that shape behavior that is aligned with the values of the Qur'an and Sunnah, both in relationships with Allah and with fellow humans. Aqidah reinforces values such as honesty, responsibility, and justice, including in the digital space, fraught with challenges like misinformation and hate speech. The study emphasizes the importance of integrating aqidah education with psychology, such as behaviorism theory, through three stages: understanding, loving, and practicing good values. Instilling aqidah from an early age is deemed critical for character development. This article offers an interdisciplinary solution to the moral challenges younger generations face, demonstrating that strong aqidah equips individuals to manage digital behavior, adhere to Islamic values, and become dignified, ethical, and responsible individuals. The study provides practical and theoretical contributions to Islamic character education relevant to the modern era.